Potensi Bakteriosin pada Bakteri Asam Laktat terhadap Staphylococcus aureus dan Escherichia coli - Sri Mastuti (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2022)
Introduction; Staphylococcus aureus and Escherichia are bacteria that usually become infested in humans. Both of these bacteria can cause diseases in the form of impetigo, food poisoning, cellulitis, and so on. Purpose; know the potential of bacteriocins in lactic acid bacteria against staphylococcus aureus and escherichia. Method: Narrative systemic review using several references from various national and international journals. Results: shows that the ability of bacteriocins in inhibiting pathogenic bacteria is expected to be an alternative to antibiotics, and can also be used as a treatment. Conclusion; That bacteriocins have a mechanism of action against the involvement of pathogenic bacteria by inhibiting cell wall synthesis, protein synthesis, nucleic acid synthesis, and major metabolic pathways. This compound is able to show the inhibitory zone in S. aureus and E bacteria